2021
DOI: 10.3390/ani11051335
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus Subtilis 29784 as a Feed Additive for Broilers Shifts the Intestinal Microbial Composition and Supports the Production of Hypoxanthine and Nicotinic Acid

Abstract: The probiotic Bacillus subtilis strain 29784 (Bs29784) has been shown to improve performance in broilers. In this study, we used a metabolomic and 16S rRNA gene sequencing approach to evaluate effects of Bs29874 in the broiler intestine. Nicotinic acid and hypoxanthine were key metabolites that were produced by the strain in vitro and were also found in vivo to be increased in small intestinal content of broilers fed Bs29784 as dietary additive. Both metabolites have well-described anti-inflammatory effects in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 66 publications
2
3
0
Order By: Relevance
“…However, adding B. subtilis to broiler diets in the present study had no impact on mRNA abundance of all the investigated cytokines and intestinal barrier proteins as well as metabolic activity of bacteria in the caecum. In accordance with the present study, adding B. subtilis ( Choi et al, 2021 ; Erinle et al, 2022 ) and grape seed extract ( Cao et al, 2020 ) to broiler diets had almost no impact on caecal microbiota and their metabolic activity. Other studies, however, have shown the effect of B. subtilis on increasing bacterial SCFA concentration in the ileum ( Aljumaah et al, 2020 ) and jejunum ( Kan et al, 2021 ) of broilers.…”
Section: Discussionsupporting
confidence: 91%
“…However, adding B. subtilis to broiler diets in the present study had no impact on mRNA abundance of all the investigated cytokines and intestinal barrier proteins as well as metabolic activity of bacteria in the caecum. In accordance with the present study, adding B. subtilis ( Choi et al, 2021 ; Erinle et al, 2022 ) and grape seed extract ( Cao et al, 2020 ) to broiler diets had almost no impact on caecal microbiota and their metabolic activity. Other studies, however, have shown the effect of B. subtilis on increasing bacterial SCFA concentration in the ileum ( Aljumaah et al, 2020 ) and jejunum ( Kan et al, 2021 ) of broilers.…”
Section: Discussionsupporting
confidence: 91%
“…Probiotics substantially increase the concentration of 5-hydroxyindole-3-acetic acid [ 70 ]. Consistent with Choi et al, the probiotic group contained higher hypoxanthine and lower lithocholic acid contents [ 71 ]. Interestingly, the levels of amino acids and their derivatives in G0D30 were substantially lower than those in G1D30, and monoacylglyceride levels in G0D30 were substantially higher than those in G1D30.…”
Section: Discussionsupporting
confidence: 84%
“…Nicotinamide supplementation has been shown to rejuvenate intestinal stem cells from aged mice by modulating the NAD/SIRT1/mTORC1 axis ( 108 ). Probiotic- and microbiota-enhanced NAD biosynthesis has been reported in microbiota-depleted mice ( 109 , 110 ). A protective effect of niacin has been demonstrated in ulcerative colitis via prostaglandin D 2 -mediated D prostanoid receptor 1 activation in dextran sulfate sodium-challenged mice ( 111 ).…”
Section: Discussionmentioning
confidence: 99%